Patient education in management of diabetes with medical comorbidities: an interventional study in South-eastern India - Devarapalli, Pradeep; Mehdiratta, Nikita; Mamillapalli, Supriya; Akella, Sruthi (International Journal of Scientific Reports, 2018)
Background: These days the effective management of diabetes has boundless challenges. Patient involvement is paramount for the successful care of diabetes. The aim of the study was to control medication adherence by providing patient education to the diabetic patients and also evaluating their drug-use, comorbidities, lifestyles and knowledge about diabetes and its management. Methods: Total 240 diabetic patients of above 18 years of age with comorbidities were included in the study, in which 128 of study group and 112 of control group. Patient’s comorbidities, drug-use and also knowledge level about diabetes was also assessed using a questionnaire. Results: Among the enrolled patients type-1 diabetes patients were 12 (5%) and 228 (95%) were type-2. Most of the patients about 25% were from age group of 40-50 years. The major number of patients has comorbidities of Systemic and coronary artery disease. Later the post counselling of test group, the mean score was 9.860±0.21 which is significant compared to pre-counselling 7.769±0.201 (p<0.001). Conclusions: The present study revealed that the patients were unaware of the basic concept related to diabetes mellitus. For better control of hyperglycaemia, there is a need for advancement of policies regard of disease education.